Branding the Sacral Landscape: Religious Content in Regional Tourism Marketing, Set in a Post-secular Society - Hilpert, Markus (The international journal of religious tourism and pilgrimage, 2020)
There is a paucity of research on the branding of sacral landscapes as a regional strategy in tourism marketing. On the one hand, the concept of place branding, to date, has been transferred very little to sacred destinations, while on the other hand, religious content and modern tourist marketing barely fit together. Nonetheless, the perception of religion in a postmodern society opens up new opportunities for sacred places to reposition themselves in the competition faced by tourist destinations. The aim of this article is to show how German tourism regions with a religious focus build their brand. Through analyzing six case studies and distilling the extant literature, this study aims to investigate whether sacral messages really do have religious depth, or whether the sacral landscape is only used superficially to attract attention.